Analisis Struktural Puisi “Walau” Karya Soetardji Calzoum Bachri - Listia Rizkiyani; Alif Abdur Rafi Deriansyah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Literary works are natural works created from human reason and desire, not without reason if literary works that are born are closely related to study and appreciation. One of the literary works that contains the author's thoughts and problems that occur in life is poetry. Poetry studies can be done from various aspects, one of which is through a structural approach. This study contains an analysis of the poem "Walau" by Soetardji Calzoum Bachri using a structural approach. This research resulted in the overall findings of physical structure and mental structure contained in the poem "Walau" by Soetardji Calzoum Bachri. The physical structure of poetry includes the form of poetry, diction, concrete words, language style, and imagery. While the inner structure of poetry includes theme, tone, atmosphere, as well as message. The method used in this study is qualitative descriptive method, while the data collection technique used is a documentation study technique.